2007
DOI: 10.1007/s11434-007-0098-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quantitative trait loci and heterotic loci for plant height using an immortalized F2 population in maize

Abstract: A set of recombinant inbred lines (RIL) derived from Yuyu22, an elite hybrid widespread in China, was used to construct an immortalized F 2 (IF 2 ) population comprising 441 different crosses. Genetic linkage maps were constructed containing 10 linkages groups with 263 simple sequence repeat (SSR) molecular markers. Twelve and ten quantitative trait loci (QTL) were detected for plant height in the IF 2 and RIL populations respectively, using the composite interval mapping method, and six same QTL were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…have reported that only 12.08% of HL (7/58) were also detected by QTL analysis. Tang et al 60. have found that 25% of QTLs and 30% of HL associated with plant height in an IF 2 population in maize had the same chromosomal locus.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that only 12.08% of HL (7/58) were also detected by QTL analysis. Tang et al 60. have found that 25% of QTLs and 30% of HL associated with plant height in an IF 2 population in maize had the same chromosomal locus.…”
Section: Discussionmentioning
confidence: 99%
“…Some HL and SL were found to be distributed in close proximity in several genomic regions (<Tang et al ; Luo et al ), indicating that clustered loci might be associated with different related traits. In our study, several loci were clustered on chromosomes A4, A8, A13, and D10.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of genetic background on QTL detection for PH and/or EH has been reported in many studies using different populations derived from various parents (Berke and Rocheford 1995; tween different generations (Veldboom and Lee 1996;Austin et al 2001;Tang et al 2006;Li et al 2007), or several testers and connected populations (Beavis et al 1991(Beavis et al , 1994Mihaljevic et al 2004;Yu et al 2006). Therefore, to generate genetic characteristics of plant-height traits at the global level, QTL mapping must be conducted using a large number of populations derived from different parents with various genetic backgrounds.…”
Section: Introductionmentioning
confidence: 98%